ANALYSIS OF THE EFFECTS OF SUPERPLASTICIZER ADDITION AND WATER REDUCTION IN CONCRETE MIXTURE ON CONCRETE COMPRESSIVE STRENGTH - Wiyanti, Dwi Sri; Laksono, Taufik Dwi (International Journal of Engineering Technologies and Management Research, 2020)
Nowadays, concrete is still one of the most used building materials, it had been improved whether in it’s quality or it’s mixture materials. There were a lot of studies that had been conducted to improve concrete that related to the produced compressive strength, stiffening speed, flexibility, etc. There are so many materials that can be used in concrete mixture to improve compressive strength. This study was conducted by using superplasticizer and reducing water amount in concrete mixture and aimed to find out how big it’s effects on the produced concrete compressive strength. Superplasticizer was used as admixture material wtih 1 percentage calculated by cement weight. Whereas water amount in concrete mixture was reduced by 0%, 15%, and 17,5%. The result obtained was that using 1% superplasticizer and reducing 15% water amount in concrete mixture produced optimum compressive strength of 22,98 Mpa.